Mot : a memoir - Einstein, Sarah (Association of Writers and Writing Programs Award for Creative Nonfiction., 2015)
At forty, Sarah Einstein is forced to face her own shortcomings. In the wake of an attempted sexual assault, she must come to terms with the facts that she is not tough enough for her job managing a local drop-in center for adults with mental illness and that her new marriage is already faltering. Just as she reaches her breaking point, she meets Mot, a homeless veteran who lives a life dictated by frightening delusion. She is drawn to the brilliant ways he has found to lead his own difficult life; traveling to Romania to get his teeth fixed because the United States doesn't offer dental care.